2017
DOI: 10.1016/j.pss.2017.01.004
|View full text |Cite
|
Sign up to set email alerts
|

Meteoroid orbits from video meteors. The case of the Geminid stream

Abstract: We use the Slovak and Czech video meteor observations, as well as video meteoroid orbits collected in the CAMS, SonotaCo, EDMOND and DMS catalogues, for an analysis of the distribution of meteoroid orbits within the stream of the Geminids and of the dispersion of their radiants. We concentrate on the influence of the measurement errors on the precision of the orbits obtained from the video networks that are based on various meteordetection software packages and various meteor orbital element softwares.The Gemi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 46 publications
1
6
0
Order By: Relevance
“…A large portion of the difference between the two was caused by the overall deceleration of the meteor, but our results suggest that at least 100 m s −1 of this difference could be due to the inherent observational biases of both systems. Finally, we note that the 200 m s −1 to 500 m s −1 initial velocity underestimation for the Geminids described by Hajdukova Jr et al (2017) is well explained by our analysis.…”
Section: Model Validationsupporting
confidence: 80%
See 1 more Smart Citation
“…A large portion of the difference between the two was caused by the overall deceleration of the meteor, but our results suggest that at least 100 m s −1 of this difference could be due to the inherent observational biases of both systems. Finally, we note that the 200 m s −1 to 500 m s −1 initial velocity underestimation for the Geminids described by Hajdukova Jr et al (2017) is well explained by our analysis.…”
Section: Model Validationsupporting
confidence: 80%
“…Hajdukova Jr et al (2017) have recently shown that most orbits of video meteors suffer from a significant bias in semi-major axis due to underestimated initial velocities. They point out that initial velocities of the Geminids are usually underestimated as much as 200 m s −1 to 500 m s −1 compared to simulations and high-precision manual reduction done by Koten et al (2004).…”
Section: Introductionmentioning
confidence: 99%
“…This core is also likely responsible for the narrow Geminids feature observed by PSP's WISPR imager (Battams et al 2020). Radar observations of smaller meteoroids (Hajduková Jr et al 2017) more subject to additional non-gravitational perturbations indicate that 1σ of the reconstructed width at the β-stream source region discussed here is ∼0.03 au.…”
Section: B Geminids β-Stream Ejection Geometrymentioning
confidence: 61%
“…The first well-documented observation of the Geminids occurred in 1862 (Greg 1872;King 1926) and this stream has been studied considerably in the last half-century, both via observations (e.g., Jenniskens 1994;Arlt & Rendtel 2006;Brown et al 2008;Jewitt & Li 2010;) and from a theoretical/modeling framework (e.g., Fox et al 1982Fox et al , 1983Ryabova 2007Ryabova , 2008Ryabova , 2016Ryabova , 2017Ryabova , 2021Williams & Ryabova 2011). Many reviews of this shower have also been undertaken in the literature (e.g., Zigo et al 2009;Jakubík & Neslušan 2015;Neslušan 2015;Hajduková et al 2017).…”
Section: Introductionmentioning
confidence: 99%